Equilibrium bank runs revisited - Ed Nosal (Federal Reserve Bank of Chicago, 2011)
Peck and Shell (2003) show that it is possible to get a bank run in a Diamond-Dybvig environment. The mechanism they use, however, is not an optimal one. When an optimal mechanism is used, the bank run equilibrium disappears.
Keywords: 330